Cardiorespiratory fitness, cardiac morphology and function, and cardiovascular risk factors in long-term breast cancer survivors compared with non-cancer controls - Mali Sæter; Sara Hassing Johansen; Kristin Valborg Reinertsen; Lene Thorsen; Kristina Hermann Haugaa; Tormod Skogstad Nilsen; Sebastian Imre Sarvari (Cardio-Oncology)
Abstract Background Although anthracycline-related cardiotoxicity is widely studied, only a limited number of echocardiographic studies have assessed cardiac function in breast cancer survivors (BCSs) beyond ten years from anthracycline treatment, and the knowledge of long-term cardiorespiratory fitness (CRF) in this population is scarce. This study aimed to compare CRF assessed as peak oxygen uptake (V̇O2), cardiac morphology and function, and cardiovascular (CV) risk factors between long-term BCSs treated with anthracyclines and controls with no history of cancer. Methods The CAUSE (Cardiovascular Survivors Exercise) trial included 140 BCSs recruited through the Cancer Registry of Norway, who were diagnosed with breast cancer stage II to III between 2008 and 2012 and had received treatment with epirubicin, and 69 similarly aged activity level-matched controls. All the participants underwent blood sampling, blood pressure measurements, echocardiography and cardiopulmonary exercise testing from October 2020 to August 2022. Results BCSs were aged 59 ± 6 years and had received a cumulative dose of 357 (243 to 366) mg/m2 of epirubicin on average 11 ± 1 years before inclusion. There was no difference between BCSs and controls with respect to peak V̇O2 (27.6 ± 5.4 mL/kg/min vs. 27.1 ± 5.4 mL/kg/min, P = 0.25), 2D left ventricular ejection fraction (57 ± 3% vs. 57 ± 3%, P = 0.43), left ventricular global longitudinal strain (-20.5 ± 1.0% vs. -20.6 ± 1.0%, P = 0.46) or the proportion with N-terminal pro-brain natriuretic peptide ≥ 125 (22% vs. 20%, P = 0.93). The proportions with hypertension, dyslipidemia or diabetes did not differ between the groups. Conclusion We found that CRF, cardiac function, and CV risk profile in BCSs examined a decade after treatment with anthracyclines were similar to that in women with no history of cancer. Trial registration clinicaltrials.gov (NCT04307407) https://clinicaltrials.gov/ct2/show/NCT04307407 .